The effect of sulfate ion on the synthesis of high octane fuel - Abdul Jalil, Aishah; Abdullah, Zalizawati; Triwahyono, Sugeng (2006)
The effect of sulfate ion (SO4 2-) loading on the properties of Pt/SO4 2--ZrO2 and catalytic isomerization of n-butane to isobutene was studied. Catalyst was prepared as follows. Zirconium hydroxide was prepared from aqueous solution of ZrOCl2Â·8H2O by hydrolysis with NH4OH aqueous solution. The precipitate was filtered and washed with deionized water followed by drying to form Zr(OH)4. SO4 2--ZrO2 was obtained by impregnation of Zr(OH)4 with H2SO4 followed by calcination at 600oC. Pt/ SO4 2--ZrO2 was obtained by impregnation of SO4 2--ZrO2 with H2PtCl6.H2O. Pyridine adsorbed FTIR and ammonia TPD were used to confirm the acid properties of Pt/SO4 2--ZrO2. Nitrogen physisorption and X-Ray Diffractometer were used to confirm the physical structures of Pt/SO4 2--ZrO2. Sample with 1.0N sulfate ion showed a catalyst with the monolayer surface of sulfate species, existence of (ZrO)3S=O (isolated structure), generation of medium acid site and presence of Broensted and Lewis acid sites. This catalyst showed high activity and stability for isomerization of nbutane to isobutene which the reaction was carried out under hydrogen atmosphere at 200oC. However, sample with 2.0N and 4.0N sulfate ion may generate H2S (poison) which may lead to deactivate catalyst rapidly during isomerization.